2003
DOI: 10.1080/00222890309602121
|View full text |Cite
|
Sign up to set email alerts
|

Distraction Affects the Performance of Obstacle Avoidance During Walking

Abstract: In this study, dual-task interference in obstacle-avoidance tasks during human walking was examined. Ten healthy young adults participated in the experiment. While they were walking on a treadmill, an obstacle suddenly fell on the treadmill in front of their left leg during either midswing, early stance, or late stance of the ipsilateral leg. Participants were instructed to avoid the obstacle, both as a single task and while they were concurrently performing a cognitive secondary task (dual task). Rates of fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(86 citation statements)
references
References 38 publications
5
78
3
Order By: Relevance
“…To avoid the obstacle during walking two distinct strategies can be utilized: the long step strategy (LSS) and short step strategy (SSS). In an LSS the obstacle is crossed by means of a lengthened crossing step while in an SSS the pre-crossing step is shortened and the obstacle is crossed in the next step (Chen et al 1994b;Weerdesteyn et al 2003Weerdesteyn et al , 2004Weerdesteyn et al , 2005. For SSS avoidance reactions, toe distance (horizontal distance from hallux marker to the edge of the obstacle in the step prior to crossing the obstacle), foot clearance (vertical distance between the foot and obstacle), and heel distance (horizontal distance between the heel marker and the edge of the obstacle in the step over the obstacle) were calculated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the obstacle during walking two distinct strategies can be utilized: the long step strategy (LSS) and short step strategy (SSS). In an LSS the obstacle is crossed by means of a lengthened crossing step while in an SSS the pre-crossing step is shortened and the obstacle is crossed in the next step (Chen et al 1994b;Weerdesteyn et al 2003Weerdesteyn et al , 2004Weerdesteyn et al , 2005. For SSS avoidance reactions, toe distance (horizontal distance from hallux marker to the edge of the obstacle in the step prior to crossing the obstacle), foot clearance (vertical distance between the foot and obstacle), and heel distance (horizontal distance between the heel marker and the edge of the obstacle in the step over the obstacle) were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…Only trials were the obstacle was released in front of the left foot were analyzed. As spatial parameters of the avoidance response are known to depend on the avoidance strategy and the phase of obstacle release (Weerdesteyn et al 2003), separate two-way (obstacle and vision) repeated measures ANOVAs with phase as the covariate were performed for an SSS (dependent variables: toe distance, foot clearance, heel distance) and an LSS (dependent variables: foot clearance, heel distance) avoidance reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allocation of attentional resources to a secondary task (transporting the object) may have been reduced during altered gait, and as a consequence this may have affected grip-inertial force precision, similar to performance decrements shown in other dual-task performances (e.g., Chen et al 1996;Müller et al 2004;Siu et al 2008;Sternad et al 2007;Weerdesteyn et al 2003). Even though grip force oscillation are usually not consciously perceived (Flanagan et al 1993), subjects may still be susceptible to temporal decrements related to the overall attention demands of a task.…”
Section: Temporal Precision Of Anticipatory Grip Force Varies Dependimentioning
confidence: 99%
“…Previous research has demonstrated the negative effects of attention shift on the performance of cognitive and motor tasks [2], [3]. A study conducted by Godell et al, [4] looked at virtual reality laparoscopic surgical simulation tasks designed to replicate the levels of cognitive and motor demands in surgical procedures, and found that there was a 30-40% increase in task completion time in the distracted vs. undistracted condition.…”
Section: Previous Workmentioning
confidence: 99%